Pelatihan Penyusunan Laporan Keuangan (Dasar-dasar Akuntansi) - Herman, Herman (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Based on partner’s pre-test data, Madrasah Aliyah students still have a relatively good level of understanding regarding the basics of accounting or financial reporting even though they are already in class XII IPS. The method used is the presentation method which contains the basics of preparing financial reports which includes simulations or examples of transaction questions until the transaction becomes a financial report. Evaluation of this service activity uses pre-test and post-test measurements. The criteria set are if the average value is 4.5 to 5, then it is in the very good category, if it is 3.5 to 4.49, then it is in the good category, if <3.5, then it is in the quite good category. Students' understanding of transaction journals, knowledge of the mechanism for posting transactions to the general ledger, knowledge related to making profit and loss reports, preparing reports on changes in capital or equity and preparing balance sheets have increased based on the pre-test and post-test measurements that have been given.